2016
DOI: 10.1093/nar/gkw506
|View full text |Cite
|
Sign up to set email alerts
|

The Pch2 AAA+ ATPase promotes phosphorylation of the Hop1 meiotic checkpoint adaptor in response to synaptonemal complex defects

Abstract: Meiotic cells possess surveillance mechanisms that monitor critical events such as recombination and chromosome synapsis. Meiotic defects resulting from the absence of the synaptonemal complex component Zip1 activate a meiosis-specific checkpoint network resulting in delayed or arrested meiotic progression. Pch2 is an evolutionarily conserved AAA+ ATPase required for the checkpoint-induced meiotic block in the zip1 mutant, where Pch2 is only detectable at the ribosomal DNA array (nucleolus). We describe here t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
101
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
2

Relationship

5
5

Authors

Journals

citations
Cited by 48 publications
(114 citation statements)
references
References 77 publications
12
101
0
1
Order By: Relevance
“…The nucleolar pool of Pch2 is unlikely to be involved in checkpoint function [41], and work in Drosophila suggests that Pch2 is associated with nuclear lamina [41, 42]. In line with previous observations [43], Pch2 was required for phosphorylation of Hop1 in checkpoint activating conditions: we observed that the abundance of Hop1 and presence of Pch2 affected the phosphorylated pool of Hop1 (for example, compare wild type, pch2 dmc1, HOP1/hop1 dmc1 and pch2 HOP1/hop1 dmc1 in Figure 2F). Combined with our findings (see also above; Figure 1) and earlier work [41], these observations suggest a dynamic exchange between non-chromosomal and chromosomal ( i.e.…”
Section: Resultssupporting
confidence: 72%
“…The nucleolar pool of Pch2 is unlikely to be involved in checkpoint function [41], and work in Drosophila suggests that Pch2 is associated with nuclear lamina [41, 42]. In line with previous observations [43], Pch2 was required for phosphorylation of Hop1 in checkpoint activating conditions: we observed that the abundance of Hop1 and presence of Pch2 affected the phosphorylated pool of Hop1 (for example, compare wild type, pch2 dmc1, HOP1/hop1 dmc1 and pch2 HOP1/hop1 dmc1 in Figure 2F). Combined with our findings (see also above; Figure 1) and earlier work [41], these observations suggest a dynamic exchange between non-chromosomal and chromosomal ( i.e.…”
Section: Resultssupporting
confidence: 72%
“…According with the prominent localization pattern of Pch2 on chromosome spreads ( Fig. 2a) (San-Segundo and Roeder 1999;Herruzo et al 2016) and with the fact that this conspicuous GFP-Pch2 structure did not overlap with Hop1-mCherry ( Fig. 4d; Fig.…”
Section: Analysis Of Pch2 Localization In Whole Meiotic Cellsmentioning
confidence: 65%
“…In this work, we have used the zip1 mutant of the budding yeast Saccharomyces cerevisiae as a genetic tool to activate the MRC. Zip1 is a major structural component of the SC central region and ZIP1 deletion impairs synapsis and crossover (CO) recombination (Dong and Roeder 2000;Borner et al 2004;Voelkel-Meiman et al 2015); as a consequence, the zip1 mutant experiences a significant MRC-dependent delay in the prophase to meiosis I transition (Herruzo et al 2016). The zip1-induced defects are detected by the Mec1-Ddc2 (ATR-ATRIP) complex, resulting in phosphorylation of the Hop1 checkpoint adaptor at several residues, including T318 (Carballo et al 2008;Refolio et al 2011;Penedos et al 2015).…”
mentioning
confidence: 99%